Prednisolone Suppresses the Extracellular Release of HMGB-1 and Associated Inflammatory Pathways in Kawasaki Disease - Ueno, Kentaro; Nomura, Yuichi; Morita, Yasuko; Kawano, Yoshifumi (Frontiers in Immunology, 2021)
Innate immune activity is believed to play an essential role in the development of Kawasaki disease (KD) vasculitis. Extracellular release of high mobility group box-1 (HMGB-1), an endogenous damage-associated molecular pattern protein that can activate the innate immune system and drive host inflammatory responses, may contribute to the development of coronary artery abnormalities in KD. Prednisolone (PSL) added to intravenous immunoglobulin treatment for acute KD may reduce such abnormalities. Here, we aimed to evaluate the dynamics of HMGB-1 and therapeutic effects of PSL on HMGB-1-mediated inflammatory pathways on KD vasculitis in vitro. Serum samples were collected prior to initial treatment from patients with KD, systemic juvenile idiopathic arthritis (sJIA), and from healthy controls (VH), then incubated with human coronary artery endothelial cells (HCAECs). Following treatment of KD serum-activated HCAECs with PSL or PBS as a control, effects on the HMGB-1 signaling pathway were evaluated. Compared to that from VH and sJIA, KD serum activation induced HCAEC cytotoxicity and triggered extracellular release of HMGB-1. KD serum-activated HCAECs up-regulated extracellular signal-regulated kinase (ERK)1/2 phosphorylation in the cytoplasm and nuclear factor kappa B (NF-κB) phosphorylation in the nucleus and increased interleukin (IL)-1β and tumor necrosis factor (TNF)-α production. PSL treatment of KD serum-activated HCAECs inhibited extracellular release of HMGB-1, down-regulated ERK1/2 and NF-κB signaling pathways, and decreased IL-1β and TNF-α production. Our findings suggest that extracellular HMGB-1 plays an important role in mediating KD pathogenesis and that PSL treatment during the acute phase of KD may ameliorate HMGB-1-mediated inflammatory responses in KD vasculitis.